Growth characterisation of InxGa1-xAs/GaAs/AIAs vertical-cavity surface-emitting laser structure using photomodulated reflectance - Choulis, Stelios A.; Hosea, Thomas Jeff Cockburn (My University, 2001)
Of crucial importance for vertical-cavity surface-emitting lasers (VCSELs) is the energy separation of the Fabry-Perot cavity mode and peak of the gain spectrum of the quantum-well (QW) active region. Since this is affected by growth variations, nondestructive characterisation of VCSEL wafers is usually required prior to full processing, to check that structures have been grown to specification. It is shown that photomodulated reflectance (PR) spectroscopy is useful for prefabrication testing of VCSEL wafers, for the example of a near-infrared InxGa1-xAs/GaAs/A1As VCSEL. By varying either the probe position on the wafer or the temperature, PR was used to study the interaction between the cavity mode and both the ground-state QW exciton and all the higher-order QW transitions. Firstly, a growth-induced shift across the wafer was exploited to tune the cavity-mode wavelength through resonance with all the QW excitonic transitions at room temperature. Secondly, by cooling from room to liquid-helium temperatures, each QW transition was blue-shifted into resonance with the cavity mode. In both methods, the PR signal was enhanced at such resonances, which could provide a sensitive way of locating 'sweet spots' on a nonuniform VCSEL wafer (where operating devices might be fabricated). Since PR can detect all the QW transitions, it is able, by comparing the measured and predicted transition energies, to provide much information about the QW cavity and growth
Keywords: Quantum wells; Light modulators; Resonance; Gallium arsenide; Indium compounds; Spectroscopy